Antimicrobial activity of different sodium and potassium salts of carboxylic acid against some common foodborne pathogens and spoilage-associated bacteria - Cabezas Pizarro, Jorge A. (2018)
Cleaning and disinfection represent the most important activities associated with the elimination of dirt and microorganisms at food processing plants. Improper procedures may lead to cross contamination of food leading to its spoilage or even the transmission of foodborne pathogens. Several strategies have been used in order to achieve a good disinfection of surfaces and products; nevertheless, microbial resistance to common-use-products has developed lately. Due to this fact, the development of new non-toxic-food compatible chemical agents that reduce the impact of foodborne pathogens and spoilage causing microorganisms is desirable for the food industry. The objective of the present study was to evaluate the antimicrobial activity of different sodium and potassium salts of aliphatic and aromatic carboxylic acid on the growth of common food spoilage and pathogenic microorganisms. Growth curves were determined for Leuconostoc mesenteroides, Lactobacillus plantarum, Enterococcus faecalis, Candida albicans, Pseudomonas aeruginosa, Salmonella Enteritidis, and Listeria monocytogenes in contact with different concentrations of carboxylic acid salts. The inhibitory effect of both aliphatic and aromatic carboxylic acid salts, in accordance with concentration levels, was 100 > 50 > 25 mg/ml. The inhibitory effect of aliphatic salts was butanoic > hexanoic> octanoic > decanoic and, benzoic > gallic > caffeic acid salts for aromatic salts. In general, sodium salts were more inhibitory than potassium salts (p ≤ 0.05).